PEMIKIRAN FAZLUR RAHMAN TENTANG PENDIDIKAN DAN RELEVANSINYA DENGAN DUNIA MODERN - Hoerul an sori (IAIN Bone, 2021)
AbstrakFazlur Rahman is one of the renewal figures in the Islamic world who contributes to develop and lure Muslim scholars in the world so that they are moved to continue their struggle to advance the quality of education, especially in the Islamic world. So in this study, the author tries to present how the role of Fazlur Rahman in developing Islamic education in the Islamic world is devoted to his thinking. The method in this study uses analytical methods with thought data processes. Alignment in the development and contribution of a Fazlur Rahman was finally stated and in line with the Constitution of the National Education System No. 20 of 2003, through its articles. In the hope that harmony can advance the quality of National education, so that Fazlur Rahman's dream of developing Islamic education can be realized in the State of Indonesia. Keywords: Fazlur Rahman, Education, Relevance, Modern World